Viscoelastic hydrogel with adjustable viscosity and application thereof in evaluating influence of hydrogel viscosity on cell behavior
Viscoelastic hydrogels with the same initial modulus but different viscosity were prepared by using covalent crosslinking and ionic crosslinking on sodium alginate, which solved the neglect of hydrogel materials in the prior art when regulating cell behavior in regulating cell behavior. The problem of viscoelastic behavior has achieved a significant impact on cell adhesion and survival, and provides application prospects for tissue repair and drug screening.
Patent Information
- Application Number
- CN202411410256.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-10
AI Technical Summary
Existing hydrogel materials ignore viscoelastic behavior when regulating cellular behavior and are difficult to regulate their viscosity to affect cellular behavior without changing matrix components.
Viscoelastic hydrogels with the same initial modulus but different viscosity were prepared by different crosslinking methods based on sodium alginate. Two different hydrogel networks were formed using covalent crosslinking and ionic crosslinking mechanisms to study the crosslinking mechanism. Effects of different viscosity changes on cell behavior.
Viscoelastic hydrogel with good biocompatibility and adjustable viscosity is achieved, which significantly affects the adhesion and survival of neural stem cells and provides application prospects in tissue repair and drug screening.
Smart Images

Figure CN119306974A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical modified and natural polymer hydrogels, and relates to a method for preparing a viscoelastic hydrogel with adjustable viscosity and an experimental verification method for regulating the behavior of neural stem cells by its viscosity. The hydrogel is suitable for regulating the adhesion of neural stem cells and is used for tissue repair, drug screening, etc. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the advancement of science and technology, bio-hydrogel preparation technology and 3D printing technology have provided a new clinical medical strategy for tissue and organ repair. Their application in the medical field includes the construction of tissue and organ substitutes, organ transplantation and regeneration, drug screening models, and anatomical models. The appropriate physical and chemical properties of hydrogel materials are the prerequisites for cell adhesion, migration, and proliferation. Therefore, hydrogel materials need to have good biocompatibility, which can not only provide a specific microenvironment for cell growth, but also serve as the basis for inducing cell functional behavior.
[0004] Gelatin is derived from the denaturation of collagen and is a widely used biomaterial with broad application prospects in the fields of cell culture, tissue engineering and 3D printing. One of the outstanding features of gelatin hydrogel is that it can serve as an excellent matrix for cell culture and tissue growth. It is similar to collagen, the basic component of the extracellular matrix, and contains many bioactive sites, especially the integrin binding sequence RGD peptide, which has good biodegradability and can regulate cell adhesion. This biocompatibility is essential in tissue engineering, and gelatin hydrogel provides a nurturing environment for the development of functional tissue structures.
[0005] Sodium alginate, which is mainly derived from abundant brown seaweed, is widely used as a base material for preparing hydrogels. Its popularity is largely due to its remarkable features such as biocompatibility, adaptable mechanical properties and rapid gelation behavior. First, sodium alginate hydrogels exhibit excellent biocompatibility, making them a first choice for a wide range of biomedical applications. This biocompatibility ensures that alginate-based constructs can interact seamlessly with living tissues and biological systems, minimizing the risk of adverse reactions or immune responses, and therefore, they are very suitable for use in regenerative medicine, tissue engineering and drug delivery. Another notable feature of sodium alginate hydrogels is their tunable mechanical properties. These hydrogels provide engineers and researchers with significant control over their mechanical properties. In addition, alginate hydrogels are known for their rapid gelation in the presence of calcium ions; at the same time, alginate can be modified to achieve photocrosslinking.
[0006] Many past studies investigating the effects of mechanical properties on cell behavior have ignored the viscoelastic behavior of the hydrogel matrix and various tissues, and used hydrogels that exhibited purely elastic behavior. Tissues such as muscle are viscoelastic. Therefore, if viscoelasticity, especially the viscosity of the hydrogel, is incorporated into the design of the hydrogel matrix, it can modulate cell behavior. Summary of the invention
[0007] In order to solve the above problems, the present invention provides a viscoelastic hydrogel with mechanical properties and adjustable viscosity based on different cross-linking methods of sodium alginate, and provides an experimental verification method for regulating the behavior of neural stem cells by its viscosity. The present invention prepares a viscoelastic hydrogel with good biocompatibility, adjustable viscosity, and rapid gelation, and proposes an experimental verification method for regulating the cell behavior by the viscosity of the viscoelastic hydrogel.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] In a first aspect of the present invention, there is provided a method for preparing viscoelastic hydrogels having the same initial modulus but different viscosities, comprising:
[0010] preparing covalently cross-linked sodium alginate-based viscoelastic hydrogel and ionically cross-linked sodium alginate-based viscoelastic hydrogel respectively;
[0011] Among them, multiple groups of covalently cross-linked viscoelastic hydrogels were obtained according to different polymerization times;
[0012] According to different ion cross-linking concentrations, multiple groups of ion cross-linked viscoelastic hydrogels are obtained;
[0013] The initial elastic moduli of multiple groups of covalently cross-linked viscoelastic hydrogels and ionically cross-linked viscoelastic hydrogels are measured. Covalently cross-linked viscoelastic hydrogels and ionically cross-linked viscoelastic hydrogels with equivalent initial elastic moduli are grouped together and the viscosity of this group of hydrogels is tested. If the viscosities of the two are different, viscoelastic hydrogels with the same initial modulus but different viscosities are obtained.
[0014] At present, any polymer material, such as gelatin, polyvinyl alcohol (PVA) and hyaluronic acid (HA), can form hydrogel by different crosslinking modes (such as physical crosslinking and chemical crosslinking), and can adjust its initial modulus to be the same. But any two hydrogels cannot ensure that the matrix components are the same, that is to say, the influence of the matrix components on cell behavior cannot be excluded. Therefore, the present invention is based on the first time that sodium alginate can realize ionic crosslinking and can realize the particularity of covalent crosslinking through modification, and utilizes these two crosslinking mechanisms to form two different hydrogel networks without changing the hydrogel matrix components. The present invention, by adjusting the two hydrogel crosslinking degrees, ensures that the hydrogel components and the matrix modulus (rigidity) are the same, and studies the different crosslinking mechanisms to cause different viscosities and thus affect cell behavior.
[0015] In some embodiments, the method for preparing a covalently cross-linked viscoelastic hydrogel comprises:
[0016] Methacryl-alginic acid, gelatin and phenyl (2,4,6-trimethylbenzoyl) lithium phosphate are uniformly mixed in a solvent to obtain a mixed solution;
[0017] The mixed solution is polymerized under ultraviolet light to obtain a covalently cross-linked viscoelastic hydrogel.
[0018] In some embodiments, the mass ratio of the methacrylated alginate, gelatin and phenyl (2,4,6-trimethylbenzoyl) lithium phosphate is 2:0.5:0.25-0.3.
[0019] In some embodiments, the method for preparing the ionically cross-linked viscoelastic hydrogel comprises:
[0020] Prepare serum-free DMEM solution containing sodium alginate and gelatin;
[0021] Prepare serum-free DMEM solution containing calcium chloride;
[0022] The serum-free DMEM solution containing calcium chloride and the serum-free DMEM solution containing sodium alginate and gelatin are mixed, and the sediment is collected to obtain an ion-crosslinked viscoelastic hydrogel.
[0023] In some embodiments, the mass ratio of sodium alginate to gelatin is 2:0.5.
[0024] In some embodiments, the concentration of calcium chloride is 24-80 mM.
[0025] A second aspect of the present invention provides the use of the above-mentioned viscoelastic hydrogels with the same initial modulus but different viscosities in evaluating the effect of hydrogel viscosity on cell behavior.
[0026] In some embodiments, the cell is a neural stem cell.
[0027] In some embodiments, the cell behaviors are cell adhesion and cell survival.
[0028] A third aspect of the present invention provides a method for evaluating the effect of viscoelastic hydrogel viscosity on neural stem cell adhesion and survival, comprising:
[0029] solidifying at least one group of viscoelastic hydrogels with the same initial modulus but different viscosities on a well plate, allowing the well plate to stand, washing, and obtaining well plates with different hydrogels solidified;
[0030] Neural stem cells were inoculated on well plates solidified with different hydrogels and cultured. The cell adhesion area and the number of live and dead cells were counted. The effect of the viscosity of the viscoelastic hydrogel on the adhesion and survival of neural stem cells was evaluated based on the statistical results.
[0031] Beneficial Effects of the Invention
[0032] (1) The present invention prepares viscoelastic hydrogels with the same initial modulus but different viscosities through two cross-linking mechanisms. The viscoelastic hydrogels have the characteristics of adjustable viscosity, good biocompatibility, and rapid gelation, and provides an experimental method for verifying the effect of viscoelastic hydrogel viscosity on cell behavior.
[0033] (2) The present invention is the first to form two different hydrogel networks based on the particularity that sodium alginate can achieve both ionic crosslinking and covalent crosslinking after modification without changing the hydrogel matrix components by utilizing these two crosslinking mechanisms. The present invention adjusts the degree of crosslinking of the two hydrogels, and studies the different viscosity caused by different crosslinking mechanisms, thereby affecting cell behavior, while ensuring that the hydrogel components and matrix modulus (rigidity) are the same. The preparation method of the present invention is simple, highly practical, and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0035] Figure 1 (a) and (b) are the chemical structures of the covalently cross-linked and ionically cross-linked sodium alginate hydrogels of the embodiments of the present invention, respectively.
[0036] Figure 2 Infrared spectra of covalently cross-linked viscoelastic hydrogel, ionically cross-linked viscoelastic hydrogel, alginic acid and methacrylated sodium alginate. 1-Light-cured covalently cross-linked hydrogel, 2-ionically cross-linked hydrogel, 3-sodium alginate, 4-methacrylated sodium alginate.
[0037] Figure 3 This is the effect of the photocrosslinking time on the storage modulus of the covalently crosslinked hydrogel according to the embodiment of the present invention.
[0038] Figure 4 For example Ca of the present invention 2+ Effect of concentration on the storage modulus of ionically cross-linked hydrogels.
[0039] Figure 5 The initial elastic moduli of three groups of hydrogels with equivalent initial elastic moduli of covalent crosslinking and ionic crosslinking mechanisms were selected.
[0040] Figure 6(a) Normalized stress relaxation curves of hydrogels with covalent crosslinking and ionic crosslinking mechanisms, (b) Changes of storage modulus and loss modulus of ionic crosslinking and covalent crosslinking hydrogels with frequency.
[0041] Figure 7 Viscosities of viscoelastic hydrogels with two cross-linking mechanisms with comparable initial moduli.
[0042] Figure 8 (a) Effect of viscoelastic hydrogel viscosity on cell adhesion area. (b) Statistics of adhesion area of neural stem cells NE-4C on viscoelastic matrices with different viscosities under the same initial modulus.
[0043] Fig. 9 (a) Representative images of live-dead staining of NE-4C neural stem cells on low-viscosity and high-viscosity viscoelastic matrices with an initial modulus of 4 kPa; (b) Viability of NE-4C neural stem cells on viscoelastic matrices with different viscosities under the same initial modulus. DETAILED DESCRIPTION
[0044] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0045] The covalently cross-linked viscoelastic hydrogel provided in an embodiment of the present invention is composed of the following substances: 2% w / v of methacryloylated alginate (AlgMA), 0.5% w / v of gelatin (Gel) (providing cell adhesion binding sites), and 0.25% w / v of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP); the ionically cross-linked viscoelastic hydrogel provided in an embodiment of the present invention is composed of the following substances: 2% w / v of sodium alginate (Alg), 0.5% w / v of gelatin (Gel) (providing cell adhesion binding sites), and 24-80 mM of calcium chloride.
[0046] The high-viscosity viscoelastic hydrogel provided by the embodiment of the present invention significantly promotes the adhesion and survival of neural stem cells, and provides broad application prospects for tissue regeneration and tissue repair.
[0047] The embodiments of the present invention provide a method for preparing a low-viscosity viscoelastic hydrogel AlgMA-Gel and a high-viscosity viscoelastic hydrogel Alg-Gel, the preparation method comprising:
[0048] Method for preparing viscoelastic hydrogel AlgMA-Gel via covalent cross-linking mechanism,
[0049] Step 1: Prepare a mixed solution containing 2% w / v of methacryloylated alginic acid (AlgMA), 0.5% w / v of gelatin, and 0.25% w / v of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP).
[0050] Step 2: Irradiate the mixed solution prepared in step 1 with ultraviolet light at 405 nm for 60 to 600 seconds to prepare hydrogels with different initial elastic moduli.
[0051] Method for preparing viscoelastic hydrogel Alg-Gel by ionic crosslinking,
[0052] Step 3: Prepare a serum-free DMEM solution containing 2% w / v sodium alginate (100 kDa) and 0.5% w / v gelatin.
[0053] Step 4: Prepare serum-free DMEM solutions containing 24 mM, 36 mM, 56 mM, and 80 mM calcium chloride solutions, respectively.
[0054] Step 5: Serum-free DMEM solutions of 24 mM, 36 mM, 56 mM, and 80 mM calcium chloride solutions and 2% w / v sodium alginate and 0.5% w / v gelatin solutions were mixed in a 5 ml injection syringe at room temperature at a volume ratio of 1:4 through a Luer lock and quickly deposited into a custom mold to obtain viscoelastic hydrogels with different ionic cross-linking concentrations.
[0055] Experimental method to obtain viscoelastic hydrogels with the same initial modulus but different viscosities via two different crosslinking mechanisms:
[0056] Step 6: The chemical structures and cross-linking mechanisms of the two proposed hydrogels were chemically verified and confirmed by Fourier transform infrared spectroscopy.
[0057] Step 7: Rheological experiments were performed to verify that changing the exposure time (covalently cross-linked hydrogel) and the ionic cross-linking concentration (ionic cross-linked hydrogel) could produce hydrogels with different moduli.
[0058] Step 8: The initial elastic modulus of the hydrogels with two cross-linking mechanisms under different illumination times (covalent cross-linking) and ionic cross-linking concentrations were measured by compression tests using a single-column mechanical testing machine. In the elastic modulus test, the gel was compressed to 20% strain at a deformation rate of 1 mm / min, and the elastic modulus was the slope of the linear stress-strain curve between 10% and 15% strain.
[0059] Step 9: Based on the experimental results of step 8, three groups of hydrogels with equivalent initial elastic modulus (covalent cross-linked hydrogels and ion cross-linked hydrogels with equivalent initial elastic modulus) are selected, and the initial elastic modulus are low, medium, and high, respectively.
[0060] Step 10: Testing the stress relaxation of the covalently cross-linked hydrogel and the ionically cross-linked hydrogel with comparable initial elastic modulus. In the stress relaxation measurement, the gel was compressed to a strain of 15% at a deformation rate of 1 mm / min, thereby keeping the strain constant, and then the stress change over time was recorded.
[0061] Step 11: Testing the initial elastic modulus and viscosity of the covalently cross-linked hydrogel and the ionically cross-linked hydrogel. The storage modulus G′ of the hydrogel after curing and the viscosity of the hydrogel were tested at a fixed frequency (f=1 Hz) and strain (γ=1%).
[0062] Experimental Methods for Modulating the Behavior of Neural Stem Cells by Viscoelastic Hydrogel Viscosity
[0063] Step 12: Experimental verification of the effect of viscoelastic hydrogel viscosity on neural stem cell adhesion.
[0064] Step 12-1: Quantitatively spread (0.2 ml / well) three groups of hydrogels with different initial moduli (low, medium and high elastic moduli) with different viscosities into a 24-well plate, solidify according to the methods of steps 2 and 5, and let stand for 2 hours.
[0065] Step 12-2: The hydrogel prepared in step 10-1 was washed twice with serum-free culture medium supplemented with 1% penicillin / streptomycin and equilibrated overnight.
[0066] Step 12-3: The cultured neural stem cells NE-4C were cultured at 10 4 Pieces / cm 2 The cells were inoculated into 24-well plates at a density of 1:40 and cultured for 24 hours. Action-TrackerGreen was diluted with PBS containing 1% BSA and 0.1% TrionX-100 at a ratio of 1:40 and stained for 45 minutes. The cells were stained with DAPI working solution (10ug / ml) for 10 minutes. The cells were washed with PBS containing 0.1% Trion X-100 several times before and after staining. The stained cells were then imaged under a 40x objective lens using an inverted fluorescence microscope, and the cell adhesion area was analyzed using Image software.
[0067] Step 13: Experimental verification of the effect of viscoelastic hydrogel viscosity on neural stem cell survival
[0068] Step 13-1: Quantitatively spread (0.2 ml / well) three groups of hydrogels with different initial moduli (low, medium and high elastic moduli) with different viscosities into a 24-well plate, solidify according to the methods of steps 2 and 5, and let stand for 2 hours.
[0069] Step 13-2: The hydrogel prepared in step 10-1 was washed twice with serum-free culture medium supplemented with 1% penicillin / streptomycin and equilibrated overnight.
[0070] Step 13-3: NE-4C neural stem cells (2×10^4 cells per square centimeter) were seeded in 24-well plates with different solidified hydrogels and cultured for 48 hours at 37°C and 5% CO2. Dead cells and live cells were stained with PI and Calcein AM, respectively. Then, the stained cells were imaged with an inverted fluorescence microscope under a 10x objective. After imaging, the number of live and dead cells was statistically analyzed using ImageJ software.
[0071] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0072] Example 1
[0073] The embodiments of the present invention provide two hydrogels - covalently cross-linked low-viscosity viscoelastic hydrogel AlgMA-Gel and ionically cross-linked high-viscosity viscoelastic hydrogel Alg-Gel and preparation methods thereof, which can obtain two viscoelastic hydrogels with the same initial elastic modulus but different viscosities, and provide an experimental verification method for regulating the behavior of neural stem cells by the viscosity of viscoelastic hydrogels.
[0074] The covalently cross-linked low-viscosity viscoelastic hydrogel AlgMA-Gel provided in an embodiment of the present invention is composed of the following substances: 2% w / v of methacryloylated alginic acid (AlgMA), 0.5% w / v of gelatin (providing cell adhesion binding sites), and 0.25% w / v of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP); the embodiment of the present invention provides an ionically cross-linked high-viscosity viscoelastic hydrogel Alg-Gel, which is composed of the following substances: 2% w / v of sodium alginate, 0.5% w / v of gelatin (Gel) (providing cell adhesion binding sites), and 24-80 mM of calcium chloride.
[0075] The high-viscosity viscoelastic hydrogel provided by the embodiment of the present invention significantly promotes cell adhesion, providing broad application prospects for tissue regeneration and tissue repair.
[0076] The embodiments of the present invention provide a method for preparing a covalently cross-linked low-viscosity viscoelastic hydrogel AlgMA-Gel and an ionically cross-linked high-viscosity viscoelastic hydrogel Alg-Gel, the preparation method comprising:
[0077] Method for preparing low viscosity viscoelastic hydrogel AlgMA-Gel by covalent crosslinking,
[0078] Step 1: Prepare a mixed solution containing 2% w / v of methacryloylated alginic acid (AlgMA), 0.5% w / v of gelatin, and 0.25% w / v of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP).
[0079] Step 2: Irradiate the mixed solution prepared in step 1 with 405 nm ultraviolet light for 60 to 600 s to prepare hydrogels with different initial elastic moduli. The chemical structure of sodium alginate covalently cross-linked hydrogel is as follows: Figure 1 As shown in (a).
[0080] Step 1 described in the above scheme is specifically as follows: 10 ml of ultrapure water is measured, 0.025 g of photoinitiator LAP is added, and the solution is heated in a water bath at 40-50° C. for 15 min, during which the solution is stirred and shaken several times to obtain a 0.25% w / v initiator standard solution; 0.05 g of gelatin is put into the initiator standard solution, and the solution is heated in a water bath at 50° C. in the dark until the gelatin is completely dissolved, and the solution is stirred and shaken to obtain a 0.5% w / v gelatin solution; 0.2 g of AlgMA (50 kDa 1.2-1.4% w / v, 300 kDa 0.6-0.8% w / v) is put into a 0.5% w / v gelatin (Gel) solution, and the solution is heated in a water bath at 50° C. in the dark until the AlgMA is completely dissolved, and the solution is stirred and shaken to obtain a 2% w / v AlgMA, 0.5% w / v gelatin mixed solution.
[0081] Step 2 of the above scheme is specifically as follows: 0.5 ml of the mixed solution prepared in step 1 is injected into a customized cylindrical hole mold with a diameter of 15 mm and a height of 2 ml, and the hydrogel mixed solution is irradiated under a handheld 405 nm ultraviolet light source for 60 to 600 s to obtain viscoelastic hydrogels with different crosslinking degrees through covalent crosslinking.
[0082] Method for preparing high viscosity viscoelastic hydrogel Alg-Gel by ionic crosslinking,
[0083] Step 3: Prepare a serum-free DMEM solution containing 2% w / v sodium alginate (100 kDa) and 0.5% w / v gelatin.
[0084] Step 4: Prepare serum-free DMEM solutions containing 24 mM, 36 mM, 56 mM, and 80 mM calcium chloride solutions, respectively.
[0085] Step 5: Serum-free DMEM solutions of 24mM, 36mM, 56mM, and 80mM calcium chloride solutions and 2% w / v sodium alginate and 0.5% w / v gelatin solutions were mixed at a volume ratio of 1:4 in a 5ml injection syringe through a Luer lock at room temperature and quickly deposited into a custom mold to obtain viscoelastic hydrogels with different ionic crosslinking concentrations. The chemical structure of sodium alginate ion-crosslinked hydrogel is shown in Figure 5. Figure 1 As shown in (b).
[0086] The step 3 is specifically as follows: 20 ml of serum-free DMEM solution is measured, 0.1 g of gelatin is added, and the solution is heated in a 40-50°C water bath to dissolve for 15 minutes, during which time the solution is stirred and shaken at 500 r / min; 0.4 g of sodium alginate is added to the gelatin standard solution, during which time the solution is stirred and shaken at 500 r / min, and the solution is heated in a 50°C water bath until the alginate is completely dissolved.
[0087] The step 4 is specifically as follows: prepare 5 10 ml serum-free DMEM solutions respectively, add 13 mg, 27 mg, 40 mg, 62 mg, and 89 mg of calcium chloride respectively, stir evenly to completely dissolve the calcium chloride, and obtain serum-free DMEM solutions of calcium chloride with concentrations of 24 mM, 36 mM, 56 mM, and 80 mM, respectively.
[0088] The step 5 is specifically as follows: 0.1 ml of 24 mM, 36 mM, 56 mM, and 80 mM calcium chloride serum-free DMEM solutions are taken respectively and mixed with 0.4 ml of 2% w / v sodium alginate and 0.5% w / v gelatin solution in a 5 ml injection syringe through a Luer lock at room temperature, and quickly deposited into a customized cylindrical hole mold with a diameter of 15 mm and a height of 2 mm to obtain viscoelastic hydrogels with different ionic crosslinking concentrations through ionic crosslinking.
[0089] Experimental method to obtain viscoelastic hydrogels with the same initial modulus but different viscosities through two different cross-linking mechanisms.
[0090] Step 6: Chemical verification and confirmation of the chemical structures and cross-linking mechanisms of the two proposed hydrogels by Fourier transform infrared spectroscopy. Figure 2 In the case of pure alginate, at 3269 cm -1 A broad absorption peak appears at 2930 cm-1, corresponding to the presence of hydrogen-bonded OH groups, and -1 The peak is due to CH stretching vibration, and the main absorption peak appears at 1594cm -1 and 1406cm -1 , is due to the asymmetric and symmetric stretching vibration of COO-. These two peaks (1594cm -1 and 1406cm -1 ) is the most useful characteristic peak for studying the ionic cross-linking process. 2+ During cross-linking, the asymmetric and symmetric -COO- vibration peaks shift to lower wavenumbers, from 1594 cm -1 and 1406cm -1 Move to 1598cm -1 and 1408cm -1 , which may be due to Ca 2+ There is a strong electrostatic interaction between sodium alginate and the carboxyl group of alginate.-1 The peak near 1680 cm is due to C=C stretching vibration. The photocrosslinking of methacryloyl alginate causes the C=C double bond in the methacryloyl group to open, so the peak at 1680 cm -1 The absorption peak near the COO disappears, and photocrosslinking may cause - The chemical environment changes, resulting in the -1 The stretching vibration peak near the -1 Therefore, chemical verification and confirmation were made by Fourier transform infrared spectroscopy. Figure 1 The chemical structures and cross-linking mechanisms of the two hydrogels are proposed.
[0091] Step 7: Rheological experiments were performed to verify that hydrogels with different moduli could be obtained by changing the UV irradiation time (covalently cross-linked hydrogel) and the ionic cross-linking concentration (ionic cross-linked hydrogel).
[0092] Rheological test: Anton Paar MCr 302 rheometer was used to perform rheological test. The test was performed at 25 °C using a 50 mm parallel plate system with a fixed gap distance of 50 μm. The hydrogels prepared with different UV irradiation times (60 s, 120 s, 300 s, 600 s) were loaded onto the fixture and time scanned at a frequency of 1 Hz with a strain of 1%. The effect of 405 nm UV irradiation time on the storage modulus (G') of AlgMA-Gel hydrogel was evaluated. Figure 3 As shown, it can be observed that G' increases with the increase of UV irradiation time, proving that the mechanical properties of AlgMA-Gel hydrogel can be adjusted by the irradiation time.
[0093] Rheological test: Anton Paar MCr 302 rheometer was used to perform rheological tests. The test was performed at 25 °C using a 50 mm parallel plate system with a fixed gap distance of 50 μm. Hydrogels prepared with different calcium ion concentrations (24 mM, 36 mM, 56 mM, 80 mM) were loaded onto the fixture and time scanned at a frequency of 1 Hz with a strain of 1%. The effect of ion concentration on the storage modulus (G') of the ion-crosslinked hydrogel Alg-Gel was evaluated. Figure 4 As shown, it can be observed that the storage modulus G' increases with the increase of ion concentration, proving that the mechanical properties of Alg-Gel hydrogel can be adjusted by ion concentration.
[0094] Step 8: The initial elastic modulus of the hydrogels with two cross-linking mechanisms under different illumination time (covalent cross-linking) and ionic cross-linking concentrations were measured by compression tests using a single-column mechanical testing machine. In the elastic modulus test, the gel was compressed to 20% strain at a deformation rate of 1 mm / min, and the elastic modulus was the slope of the linear stress-strain curve between 10% and 15% strain. Each parameter was repeated 3 times.
[0095] Elastic modulus test: According to step 8, the elastic moduli of the covalently cross-linked hydrogels at different illumination times and the ionically cross-linked hydrogels at different ion concentrations were tested as shown in Table 1. It can be observed that the initial elastic modulus of the covalently cross-linked hydrogel AlgMA-Gel increases with the increase of illumination time, and the initial modulus of the ionically cross-linked hydrogel Alg-Gel increases with the increase of ion concentration.
[0096] Table 1 Elastic modulus of covalently cross-linked hydrogels at different illumination times and ionically cross-linked hydrogels at different ion concentrations
[0097]
[0098] Step 9: Based on the experimental results of step 8, three groups of hydrogels with equivalent initial elastic modulus (covalent cross-linked hydrogel and ion-cross-linked hydrogel have equivalent initial elastic modulus) are selected, and the initial elastic moduli are low (covalent cross-linked hydrogel AlgMA 2% (300kDa 0.6%, 50kDa 1.4%)-Gel 0.5% with an illumination time of 60s and ion-cross-linked hydrogel Alg (100kDa) 2%-Gel 0.5% with an ion concentration of 24mM), medium (covalent cross-linked hydrogel AlgMA 2% (300kDa 0.6%, 50kDa 1.4%)-Gel 0.5% with an illumination time of 600s and ion-cross-linked hydrogel Alg (100kDa) 2%-Gel 0.5% with an ion concentration of 36mM), and high (covalent cross-linked hydrogel AlgMA 2% (300kDa0.8%, 50kDa 1.4%)-Gel 0.5% with an illumination time of 300s). 1.2%)-Gel 0.5% and ion crosslinked hydrogel Alg (100 kDa) 2%-Gel 0.5% with an ion concentration of 56 mM. The initial moduli of the three groups of hydrogels with similar initial moduli of the two crosslinking mechanisms are as follows: Figure 5 shown.
[0099] Step 10: Further, the stress relaxation of the covalently cross-linked hydrogel and the ionically cross-linked hydrogel with the same initial elastic modulus was tested. In the stress relaxation measurement, the gel was compressed to a strain of 15% at a deformation rate of 1 mm / min, thereby keeping the strain constant, and then the stress change over time was recorded. Figure 6The initial elastic modulus shown in (a) is similar. The stress relaxation of covalently cross-linked hydrogels and ionically cross-linked hydrogels is different. The stress relaxation of covalently cross-linked hydrogels is slower than that of ionically cross-linked hydrogels. Both ionically cross-linked and photo-cross-linked hydrogels are viscoelastic materials. The stress relaxation of photo-cross-linked hydrogels is smaller than that of elastic materials, which is confirmed by the frequency independence of the shear storage modulus. Figure 6 (b) Ionically (calcium ion) cross-linked hydrogels show strong stress relaxation as the hydrogel reorganizes over time, as evidenced by the frequency dependence of the shear storage modulus. Figure 6 In (b), this occurs because the ionic crosslinkers are reversible and can dissociate and recombine when stress is applied to the hydrogel.
[0100] Step 11: Testing the viscosity of covalently crosslinked hydrogels and ionically crosslinked hydrogels with comparable initial elastic moduli. The viscosity of the two hydrogels with comparable initial moduli after curing was tested at a fixed frequency (f = 1 Hz) and strain (γ = 1%). Figure 7 shown.
[0101] Experimental Methods for Modulating the Behavior of Neural Stem Cells by Viscoelastic Hydrogel Viscosity
[0102] Step 12: Experimental verification of the effect of viscoelastic hydrogel viscosity on neural stem cell adhesion.
[0103] Step 12-1: Quantitatively spread (0.2 ml / well) three groups of hydrogels with different initial moduli (low, medium and high elastic moduli) with different viscosities into a 24-well plate, solidify according to the methods of steps 2 and 5, and let stand for 2 hours.
[0104] Step 12-2: The hydrogel prepared in step 10-1 was washed twice with serum-free culture medium supplemented with 1% penicillin / streptomycin and equilibrated overnight.
[0105] Step 12-3: The cultured neural stem cells NE-4C were cultured at 10 4 Pieces / cm 2 The cells were inoculated into a 24-well plate at a density of 1:40 and cultured for 24 hours. Action-TrackerGreen was diluted with PBS containing 1% BSA and 0.1% TrionX-100 at a ratio of 1:40 and stained for 45 minutes. The cells were stained with DAPI working solution (10ug / ml) for 10 minutes. During this period, the cells were washed with PBS containing 0.1% Trion X-100 several times before and after staining. The stained cells were then imaged under a 40x objective lens using an inverted fluorescence microscope, and the cell adhesion area was analyzed using Image software. Figure 8(a) shows the adhesion state of neural stem cells NE-4C on two viscoelastic hydrogel substrates with low and high viscosities of ~1.7kPa, ~4kPa, and ~7.2kPa respectively. It can be clearly observed that the viscosity of the viscoelastic matrix significantly affects the adhesion and spreading of neural stem cells. On the matrix with higher viscosity, the spreading area of neural stem cells increases, and more synapse-like structures are formed. The cell adhesion area statistics are shown in Figure 2. Figure 8 As shown in (b), under the same initial modulus, increasing the viscosity of the viscoelastic matrix can increase the cell adhesion area. Ion-crosslinked matrices have faster stress relaxation and higher dynamic viscosity characteristics, while covalently crosslinked matrices exhibit more stable but relatively low viscosity. For high-viscosity ion-crosslinked matrices, the dynamic characteristics of ionic bonds enable cells to produce greater adhesion in a higher viscosity environment. Specifically, higher viscosity can prolong the contact time between the cell membrane and the matrix and increase the life span of integrin-ligand binding on the cell membrane at the molecular level. This extended contact time and increased molecular stability enhance the remodeling of the cytoskeleton, thereby promoting the adhesion, spreading and synapse formation of neural stem cells. For low-viscosity covalently crosslinked matrices, the molecular bonds are subject to greater thermal disturbances, resulting in reduced cell adhesion stability.
[0106] Step 13: Experimental verification of the effect of viscoelastic hydrogel viscosity on neural stem cell survival
[0107] Step 13-1: Quantitatively spread (0.2 ml / well) three groups of hydrogels with different initial moduli (low, medium and high elastic moduli) with different viscosities into a 24-well plate, solidify according to the methods of steps 2 and 5, and let stand for 2 hours.
[0108] Step 13-2: The hydrogel prepared in step 10-1 was washed twice with serum-free culture medium supplemented with 1% penicillin / streptomycin and equilibrated overnight.
[0109] Step 13-3: NE-4C neural stem cells (2×10^4 cells per square centimeter) were seeded in 24-well plates with different solidified hydrogels and cultured for 48 hours at 37°C and 5% CO2. Dead cells and live cells were stained with PI and Calcein AM, respectively. Then, the stained cells were imaged with an inverted fluorescence microscope under a 10x objective. After imaging, the number of live and dead cells was statistically analyzed using ImageJ software. Fig. 9(a) shows the live-dead staining fluorescence microscopy images of NE-4C neural stem cells on low-viscosity and high-viscosity viscoelastic matrices with an initial modulus of 4 kPa. The results show that the number of live cells on the high-viscosity viscoelastic matrix is significantly higher than that on the low-viscosity matrix. In addition, the quantitative analysis of cell viability on low-viscosity and high-viscosity matrices with initial moduli of 1.8 kPa, 4 kPa, and 7.2 kPa is shown in Figure 2. Fig. 9 As shown in (b). The results show that under the same initial modulus conditions, the survival rate of cells on high viscosity matrix is significantly higher than that on low viscosity matrix, increasing by 17.9%, 15.2% and 19.5% respectively. This phenomenon shows that the viscosity of the matrix has an important influence on the survival of NE-4C neural stem cells, and within a certain range, the increase of matrix viscosity helps to improve the survival rate of cells.
[0110] The viscoelastic hydrogel with the same initial modulus but different viscosities prepared by two cross-linking mechanisms and the experimental verification method of the effect of viscosity on the behavior of neural stem cells can be used in tissue engineering, tissue repair, medicine and the like.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing viscoelastic hydrogels having the same initial modulus but different viscosities, characterized in that: include: preparing covalently cross-linked sodium alginate-based viscoelastic hydrogel and ionically cross-linked sodium alginate-based viscoelastic hydrogel respectively; Among them, multiple groups of covalently cross-linked viscoelastic hydrogels were obtained according to different polymerization times; According to different ion cross-linking concentrations, multiple groups of ion cross-linked viscoelastic hydrogels are obtained; The initial elastic moduli of multiple groups of covalently cross-linked viscoelastic hydrogels and ionically cross-linked viscoelastic hydrogels are measured. Covalently cross-linked viscoelastic hydrogels and ionically cross-linked viscoelastic hydrogels with equivalent initial elastic moduli are grouped together and the viscosity of this group of hydrogels is tested. If the viscosities of the two are different, viscoelastic hydrogels with the same initial modulus but different viscosities are obtained.
2. The viscoelastic hydrogel with adjustable viscosity according to claim 1, characterized in that: The method for preparing the covalently cross-linked viscoelastic hydrogel comprises: Methacryl-alginic acid, gelatin and phenyl (2,4,6-trimethylbenzoyl) lithium phosphate are uniformly mixed in a solvent to obtain a mixed solution; The mixed solution is polymerized under ultraviolet light to obtain a covalently cross-linked viscoelastic hydrogel.
3. The viscoelastic hydrogel with adjustable viscosity according to claim 1, characterized in that: The mass ratio of the methacrylated alginate, gelatin and phenyl (2,4,6-trimethylbenzoyl) lithium phosphate is 2:0.5:0.25-0.
3.
4. The viscoelastic hydrogel with adjustable viscosity according to claim 1, characterized in that: The preparation method of the ion-crosslinked viscoelastic hydrogel comprises: Prepare serum-free DMEM solution containing sodium alginate and gelatin; Prepare serum-free DMEM solution containing calcium chloride; The serum-free DMEM solution containing calcium chloride and the serum-free DMEM solution containing sodium alginate and gelatin are mixed, and the sediment is collected to obtain an ion-crosslinked viscoelastic hydrogel.
5. The viscoelastic hydrogel with adjustable viscosity according to claim 4, characterized in that: The mass ratio of sodium alginate to gelatin is 2:0.
5.
6. The viscoelastic hydrogel with adjustable viscosity according to claim 4, characterized in that: The concentration of the calcium chloride is 24-80 mM.
7. Use of the viscoelastic hydrogels of any one of claims 1 to 6 having the same initial modulus but different viscosities in evaluating the effect of hydrogel viscosity on cell behavior.
8. The use according to claim 7, characterized in that The cells are neural stem cells.
9. The use according to claim 7, characterized in that The cell behaviors are cell adhesion and cell survival.
10. A method for evaluating the effect of viscoelastic hydrogel viscosity on neural stem cell adhesion and survival, comprising: solidifying at least one group of viscoelastic hydrogels with the same initial modulus but different viscosities on a well plate, allowing the well plate to stand, washing, and obtaining well plates with different hydrogels solidified; Neural stem cells were inoculated on well plates solidified with different hydrogels and cultured. The cell adhesion area and the number of live and dead cells were counted. The effect of the viscosity of the viscoelastic hydrogel on the adhesion and survival of neural stem cells was evaluated based on the statistical results.
Citation Information
Patent Citations
Hydrogel as well as preparation method and application thereof
CN105771004A
Ultra-long tensile self-repairing hydrogel bonding material and preparation method thereof
CN110724282A
Bi-crosslinking viscoelastic hydrogel as well as preparation method and application thereof
CN117100915A
Cross-linked hyaluronic acid-laminin gels and use thereof in cell culture and medical implants
US20050260753A1
The combined influence of viscoelastic and adhesive cues on fibroblast spreading and focal adhesion formation
US20240157023A1
Cited By
Method for determining content of photoinitiator in cell culture fish meat
CN120064518A